Clarifying, developing and valuing the role of unit coordinators as informal leaders of learning in higher education. - Roberts, Susan; Butcher, Linda; Brooker, Miriam (Australian Learning and Teaching Council, 2011)
This study provides an evidence-based job description that clarifies the role of the Unit Coordinator (also known as Unit Chair, Unit Convenor, Course Coordinator, Subject Coordinator, and Programme Coordinator at universities around Australia) and highlights the role's fundamental learning leadership components. A person specification of the competencies and capabilities needed to perform the role effectively has been developed, as have unilateral criteria for probationary, performance and promotional reviews. Induction and professional development proformas have also been devised to facilitate the provision by universities of targeted support for new and experienced Unit Coordinators. [Executive summary]